Language Acquisition on Internet Addiction Disorder Children - Harmoko, Danang Dwi; Purwaningrum, Prapti Wigati (Jurnal Dakwah dan Komunikasi, 2024)
The COVID-19 pandemic has increased the intensity of handling children with screens connected to the internet. This has resulted in an increase in cases of IAD (Internet Addiction Disorder) in children. This study aims to determine language acquisition in children with IAD (Internet Addiction Disorder). This research uses a descriptive qualitative approach. The data were obtained through direct observation and experimentation with the research subjects, namely children who were in language acquisition (aged 4-5 years). There are several findings in this study. The first finding is differences in language mastery in children before and during the Covid 19 pandemic. Differences influence this in language input where during the pandemic, children's language input was dominated by the media. The following finding is that children with IAD experience several obstacles in mastering language, such as difficulties in making argumentative sentences, comparative sentences, and assembling sentences in complex stories. Besides that, the following finding is that children with IAD tend to acquire a diverse vocabulary, some of which are not according to age. Through these findings, the researcher calls for the active role of stakeholders such as the government, parents, community, and academics in anticipating the negative impacts of excessive internet use.